Is Social Media Contributing to an Unhealthy Fixation with Health? - Lanitis Antigone; Raspin Courtney (International Journal of Eating and Weight Disorders, 2020)
Orthorexia Nervosa (ON) describes a pathological, unhealthy fixation with eating healthy food. This study intends to further understand ON and its possible link to the use of social media, and specifically, to test the prevalence of ON in an opportunity sample with the use of two ON measures – the ORTO-15 and the Tereul Orthorexia Scale (TOS); to use and validate a new ON measure (TOS); to examine the relationship between ON and social media use, with a focus on Instagram users; and to further understand the participants’ interpretations of the possible link between eating patterns and social media use. This study uses a convergent design and a mixed methods approach, which employs both statistical and thematic analysis (TA). Data from 201 participants suggested a high prevalence of ON across the sample, and the results also reinforced the validity of the TOS measure (α = .86). ORTO-15 scores showed significant differences between age groups, genders, and Instagram users and non-Instagram users. The TA generated three overall themes: ‘The Importance of Belonging’, ‘Health as Art’ and ‘Craving’. The high prevalence in the sample may have been a result of the researcher’s recruitment method, and the ON measures may have categorised individuals on non-medically prescribed diets as ‘orthorexic’. Both the quantitative and qualitative results offer evidence to support a possible link between ON and social media use, specifically Instagram. Further research should be done to establish official criteria and measures for ON and the effect of social media on eating patterns.
Keywords: Orthorexia Nervosa